In situ sediment temperature measurements for geothermal heat flow estimates, cruise PS134 - Caroline Brand; Norbert Kaul; Mareen Lösing; Karsten Gohl (PANGAEA, 2025)
In situ sediment temperatures measured during cruise PS134 on the Bellingshausen Sea Shelf. Five Miniaturized Temperature Data-Loggers (MTL) were mounted on a 5 m lance for measuring sediment temperatures. One MTL was mounted on the weight head (Sensor 0) and reports here the bottom water temperature.
In: Brand, C et al. (2025): Geothermal heat flow data collected during PS134 [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.984026